Postoperative cognitive functions in patients with benign intracranial lesions - Stefanie Bette; Julia M. Ruhland; Benedikt Wiestler; Melanie Barz; Bernhard Meyer; Claus Zimmer; Yu-Mi Ryang; Florian Ringel; Jens Gempt (Scientific Reports, 2021)
Abstract The aim of this study was to assess pre- and postoperative cognitive functions in patients who underwent surgery for benign intracranial lesions. In total, 58 patients (21 men, 37 women, mean age 51.6 years [range 24–76 years]) with benign intracranial lesions (including benign tumors and vascular lesions) and neuralgia of the trigeminal nerve were included in this prospective study. Extensive cognitive testing was used to categorize attention, memory, and executive functions. Mood and pain were assessed preoperatively (t0, mean 3.7 days before surgery), immediately after surgery/during inpatient stay (t1, mean 7.6 days after surgery), and at first outpatient check-up (t2, mean 99.5 days after surgery). All 58 patients were tested at t0 and t1, but at t2 only 24 patients were available at t2. The data were categorized as improvement/stable condition or deterioration and shown as percentages. The pre- and postoperative values of BDI-II and mood were compared by the Wilcoxon test for paired samples. Binary logistic regression analyses were performed to identify parameters influencing cognition in the subgroup of meningioma patients. Immediately after surgery (t1), the percentage of patients with improvement/stable condition was > 50% in all categories in the majority of subtests (attention: 12/14 subtests, memory: 11/13 subtests, executive functions: 6/9 subtests). Similar results were shown at t2. Mood and pain did not change significantly after surgery. Factors like age, Karnofsky performance status, and tumor volume were not shown as significant influencing factors for cognitive functions in meningioma patients. The results of this study suggest that—in contrast to neuroepithelial tumors—cognitive functions do not deteriorate after surgery of benign intracranial lesions. Further studies are necessary to evaluate the results of this study.